Regulation of Secondary Metabolite Biosynthesis: Catabolite Repression of Phenoxazinone Synthase and Actinomycin Formation by Glucose - Gallo, Maria (1972)
Synthesis of the secondary metabolite, actinomycin, and the enzyme, phenoxazinone synthase, involved in the biosynthesis of the antibiotic, were shown to be under severe catabolite repression by glucose. Of a variety of hexoses and carbon compounds examined, glucose, and to a lesser extent, mannose, proved to be the most repressive for enzyme synthesis. The repression by glucose was most evident before production of the antibiotic. In a chemically defined medium suitable for actinomycin production, synthesis of phenoxazinone synthase began at the time the glucose (0.1%) supply was depleted. Soon after, antibiotic synthesis was initiated. Galactose, the major carbon source for growth and antibiotic synthesis, was not utilized until the glucose was consumed. Generally, carbon compounds which supported a rapid rate of growth were most effective in producing catabolite repression.